The resting-state brain activity signatures for addictive disorders - Zheng, Hui; Zhai, Tianye; Lin, Xiao; Dong, Guangheng; Yang, Yihong; Yuan, Ti-Fei (Med (New York, N.Y. : Online), 2024)
Addiction is a chronic and relapsing brain disorder. Despite numerous neuroimaging and neurophysiological studies on individuals with substance use disorder (SUD) or behavioral addiction (BEA), currently a clear neural activity signature for the addicted brain is lacking. We first performed systemic coordinate-based meta-analysis and partial least-squares regression to identify shared or distinct brain regions across multiple addictive disorders, with abnormal resting-state activity in SUD and BEA based on 46 studies (55 contrasts), including regional homogeneity (ReHo) and low-frequency fluctuation amplitude (ALFF) or fractional ALFF. We then combined Neurosynth, postmortem gene expression, and receptor/transporter distribution data to uncover the potential molecular mechanisms underlying these neural activity signatures. The overall comparison between addiction cohorts and healthy subjects indicated significantly increased ReHo and ALFF in the right striatum (putamen) and bilateral supplementary motor area, as well as decreased ReHo and ALFF in the bilateral anterior cingulate cortex and ventral medial prefrontal cortex, in the addiction group. On the other hand, neural activity in cingulate cortex, ventral medial prefrontal cortex, and orbitofrontal cortex differed between SUD and BEA subjects. Using molecular analyses, the altered resting activity recapitulated the spatial distribution of dopaminergic, GABAergic, and acetylcholine system in SUD, while this also includes the serotonergic system in BEA. These results indicate both common and distinctive neural substrates underlying SUD and BEA, which validates and supports targeted neuromodulation against addiction. This work was supported by the National Natural Science Foundation of China and Intramural Research Program of the National Institute on Drug Abuse, National Institutes of Health. [Display omitted] •There are shared or distinct brain regions across different addictive disorders•Addiction increased activity in the striatum and SMA•Addiction decreased activity in ACC and vmPFC•Altered neural activity associated with dopamine receptor signaling pathway This study aimed to uncover common and unique patterns of abnormal brain activity in individuals with substance use disorder (SUD) and behavioral addiction (BEA). Understanding these patterns is crucial for addressing addiction, a persistent condition with complex neural mechanisms. The findings reveal shared alterations in striatum and motor cortex activities, as well as reduced activity in the anterior cingulate cortex and ventromedial prefrontal cortex for both SUD and BEA. These results highlight the importance of targeted neuromodulation approaches. In simplified terms, the study explores brain activity in addiction, emphasizing shared and distinct patterns in SUD and BEA and providing insights for targeted interventions. Zheng et al. identified shared and unique brain activity patterns in substance use disorder and behavioral addiction, providing new mechanistic insights and treatment targets with brain stimulation.